2014
DOI: 10.1038/nrurol.2014.42
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer in Asian men

Abstract: Prostate cancer incidence and mortality in most native Asian populations have gradually increased, but are around one-third lower than in corresponding Asian-American cohorts, which are themselves lower than the rates observed in other American cohorts. Although genetic and environmental factors, particularly a Western diet, could partially explain these differences, lower exposure to PSA screening in Asian individuals might be a major contributing factor. Genetic features and diet are, however, unlikely to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
195
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 236 publications
(197 citation statements)
references
References 65 publications
1
195
1
Order By: Relevance
“…According to recent meta-analyses on autopsy studies, age-adjusted rates of latent PC have remained fairly constant over time (1,12). Recently, some reports suggest that the incidence of PC has increased in Asian countries (11,14). In Japan, according to The Center for Cancer Control and Information Services in Japan, the morbidity rate (per 100 000 population) of PC has increased in these ten years, from 47.1 in 2002 to 126.6 in 2011 (4).…”
mentioning
confidence: 99%
“…According to recent meta-analyses on autopsy studies, age-adjusted rates of latent PC have remained fairly constant over time (1,12). Recently, some reports suggest that the incidence of PC has increased in Asian countries (11,14). In Japan, according to The Center for Cancer Control and Information Services in Japan, the morbidity rate (per 100 000 population) of PC has increased in these ten years, from 47.1 in 2002 to 126.6 in 2011 (4).…”
mentioning
confidence: 99%
“…Prostate cancer (PCa) is the most common cancer in males in Western countries and its incidence has increased in Japan (1). Androgen deprivation therapy (ADT) with gonadotropinreleasing hormone (GnRH) agonists, GnRH antagonists or bilateral orchiectomy is a well-established treatment for advanced PCa (2).…”
mentioning
confidence: 99%
“…A study by Miyamoto et al 39 showed a 5-year OS of 62.5% in a cohort of 79 metastatic CSPC Japanese patients on ADT, a number much higher than that in the ADT-only arm for metastatic CSPC patients in the STAMPEDE trial (5-year OS 39%), which only enrolled UK and Swiss patients. 34 It has been proposed that differences in OS amongst metastatic CSPC patients on ADT might arise, because countries with rigorous screening processes might detect most cancers before they metastasize, 51 It is therefore plausible that patients with these more aggressive cancers might also derive more benefit from docetaxel compared with patients in countries with less stringent screening programs.…”
Section: Discussionmentioning
confidence: 99%